Learning curve and established phase for uniportal VATS lobectomies: the Papworth experience - Bedetti, Benedetta; Bertolaccini, Luca; Solli, Piergiorgio; Scarci, Marco (Journal of Thoracic Disease; Vol 9, No 1 (January 24, 2017): Journal of Thoracic Disease, 2017)
Background: Uniportal video-assisted thoracoscopy (VATS) has increasingly gained importance in the thoracic surgery scenario. The use of this technique can reduce postoperative pain and length of stay and gives the surgeon the same operative perspective as open surgery. Methods: We retrospectively analysed the data of 73 patients who underwent uniportal VATS lobectomies from November 2014 to December 2015 in our institution. We divided the patients in two groups (group 1: first 30 patients vs. group 2: established phase, 43 patients) to compare and evaluate the data regarding the learning curve. To explore evolution of learning curve, data were plotted to calculate Spearman’s Rank-Order Correlation. R (version 3.2.3) was used for statistical analysis. Results: The median age was 69.9 (group 1) and 68.8 (group 2) years. Mean operative time was 84.9±33.0 (group 1) and 84.8±31.5 (group 2) minutes. The conversion rate was 13.3% in group 1 vs. 9.3% in group 2, showing a significant learning reduction (rho=0.590). Overall morbidity rate was 15.1%. The most common complication consisted in prolonged air leak. Interpolation line of complications showed a significant decrease due to learning curve (rho=0.676). The median length of stay was 4 days in group 1 vs. 3 days in group 2. The 30-day mortality was 3.3% in group 1 and 0% in group 2. Conclusions: The comparison between the groups showed that the median length of stay, operative time, conversion rate and 30-day mortality statistically significantly improved in the established phase. Also, complications like prolonged air leak were decreasing in the established phase. In conclusion, the uniportal VATS lobectomy technique can be performed safely from experienced surgeons without major complications and with an acceptable mortality rate.